A Bacillus velezensis strain shows antimicrobial activity against soilborne and foliar fungi and oomycetes - Wockenfuss, Anna; Chan, Kevin; Cooper, Jessica G.; Chaya, Timothy; Mauriello, Megan A.; Yannarell, Sarah M.; Maresca, Julia A.; Donofrio, Nicole M. (Frontiers in Fungal Biology, 2024)
Biological control uses naturally occurring antagonists such as bacteria or fungi for environmentally friendly control of plant pathogens. Bacillus spp. have been used for biocontrol of numerous plant and insect pests and are well-known to synthesize a variety of bioactive secondary metabolites. We hypothesized that bacteria isolated from agricultural soil would be effective antagonists of soilborne fungal pathogens. Here, we show that the Delaware soil isolate Bacillus velezensis strain S4 has in vitro activity against soilborne and foliar plant pathogenic fungi, including two with a large host range, and one oomycete. Further, this strain shows putative protease and cellulase activity, consistent with our prior finding that the genome of this organism is highly enriched in antifungal and antimicrobial biosynthetic gene clusters. We demonstrate that this bacterium causes changes to the fungal and oomycete hyphae at the inhibition zone, with some of the hyphae forming bubble-like structures and irregular branching. We tested strain S4 against Magnaporthe oryzae spores, which typically form germ tubes and penetration structures called appressoria, on the surface of the leaf. Our results suggest that after 12 hours of incubation with the bacterium, fungal spores form germ tubes, but instead of producing appressoria, they appear to form rounded, bubble-like structures. Future work will investigate whether a single antifungal molecule induces all these effects, or if they are the result of a combination of bacterially produced antimicrobials.